Field notes on science & nature - Canfield, Michael R. (Harvard University Press, 2011)
Pioneering a new niche in the study of plants and animals in their natural habitat, this book allows readers to peer over the shoulders and into the notebooks of a dozen eminent field workers, to study firsthand their observational methods, materials, and fleeting impressions.